D’Future Tent / Ariff Hakimi Hasbullah … [et al.] - Hasbullah, Ariff Hakimi; Rozhan, Intan Shafiqah Adleena; Muhamad Ikbal, Ahmad Syahir; Azian, Nur Sarah Izzati; Omar, Siti Nazirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Most of the tents sold on the market are just for temporary shelter with not so much regard in the aspect of comfortability. For example, not all campsites have level ground whereas we have to sleep on cold uneven ground. Besides, there’s no power to charge our devices. However not everyone is keen to live in an uncomfortable situation even for a brief moment including us. Thus we have set our goal and are determined to provide the best tent for everyone to enjoy the outdoor breathtaking sceneries without sacrificing the comfortability. We won’t stop by just providing comfort, to make sure we can create a huge impact on the scene, we also include some of never seen before novelties on traditional tents to our product, that is, fabrics that can harvest solar energy, and are trackable using RFID technology. We also won’t neglect our responsibilities to our community, we aim to provide our tents to the government agencies and non-profit organizations for disaster relief measures and to tackle the refugee crisis of lack of shelters. With all being said, surely D’Future tent has a bright future for commercialization due to the novelty features and the usage are suitable for any possible situation.